Microbial rhamnolipid production: a critical re-evaluation of published data and suggested future publication criteria - Irorere, Victor U. (Appl Microbiol Biotechnol, 2017)
High production cost and potential pathogenicity of Pseudomonas aeruginosa, commonly used for rhamnolipid synthesis, have led to extensive research for safer producing strains and cost-effective production methods. This has resulted in numerous research publications claiming new non-pathogenic producing strains and novel production techniques many of which are unfortunately without proper characterisation of product and/or producing strain/s. Genes responsible for rhamnolipid production have only been confirmed in P. aeruginosa, Burkholderia thailandensis and Burkholderia pseudomallei. Comparing yields in different publications is also generally unreliable especially when different methodologies were used for rhamnolipid quantification. After reviewing the literature in this area, we strongly feel that numerous research outputs have insufficient evidence to support claims of rhamnolipid-producing strains and/or yields. We therefore recommend that standards should be set for reporting new rhamnolipid-producing strains and production yields. These should include (1) molecular and bioinformatic tools to fully characterise new microbial isolates and confirm the presence of the rhamnolipid rhl genes for all bacterial strains, (2) using gravimetric methods to quantify crude yields and (3) use of a calibrated method (high-performance liquid chromatography or ultra-performance liquid chromatography) for absolute quantitative yield determination.